PROBLEMS OF TURKMEN GAS EXPORT: IEW FROM UKRAINE - PREYGER, David; OMELCHENKO, Vladimir (CENTRAL ASIA AND THE CAUCASUS, 2007)
There has been a perceptible increase recently in the public’s attention to the energy security problems of the European continent (primarily of the member states of the European Union), particularly with respect to supplying its national economies with natural gas. This was the topic of a discussion arousing great interest at the St. Petersburg G-8 Summit held in July 2006.and it is still drawing the attention of participants in numerous highest-level bi- and multilateral meetings from the Russian Federation, Germany, the leadership of the European Commission, Poland, Ukraine, the states of Central Asia and the Caspian Region, the Middle East, and North Africa. The Russian Federation’s guaranteed delivery of natural gas in the future was the most widely discussed topic. Russia currently accounts for more than one quarter of the total volume of the EU member states’ import purchases. In mid-November 2006, the results of a confidential study of gas dependence on Russia carried out by NATO economist experts were published in the mass media (the document was sent to the ambassadors of all 26 member states of the alliance). This document maintains that the RF may try to create a gas cartel consisting of Algeria, Qatar, Libya, the Central Asian countries, and, possibly, Iran. Against the background of the discussion that unfolded, the interest in states transiting raw hydrocarbons to Europe declined somewhat, although certain European countries (primarily Poland) are trying to prevent this by drawing attention to the role they play in ensuring uninterrupted deliveries of natural gas to Europe from the East.